JUNGEAN CONCEPT OF QUATERNITY AND THE FEMININE ASPECT IN THE TRINITY - Kadankavil, K.T. (Journal of Dharma, 1980)
Though more than a quarter century ago C.O. Jung came forward with certain startling theories concerning the Christian dogma of Trinity, the theological as well as the scientific world have practically ignored them, and consequently his writings did not initiate any new theologizing Jung naturally expected in the Christian West. For most of the scientists what Jung wrote was no science, and for the theologians his theories were wild speculations on theological matters without reliable scriptural foundations. The present article is an attempt to discuss Jung’s claim that psychologically at least opposites such as good and evil, male and female are united in one God.